Avaliação da atividade reprodutiva e de biomarcadores de impacto ambiental no lambari Astyanax fasciatus do reservatório de Furnas, Rio Grande, Minas Gerais - Paula Suzanna Prado (2010)
In order to assess the aquatic pollution by domestic, industrial and agriculture wastes in the Furnas Reservoir, Grande River, fish catchings were conducted at five sampling sites during 2006 and 2007. A range of health and reproductive biomarkers from molecular to population levels were evaluated in feral characid Astyanax fasciatus and related to environmental pollution. Fish from the reference site (Turvo) exhibited the best health and reproductive status, while several adverse effects were detected at the contaminated sites. Compared to the reference site, the hepatosomatic index was significantly higher in all impacted sites. At the Barranco Alto and Fama sites, fish showed reduced body growth, delayed gonadal maturation and a lower gonadosomatic index which were associated to pollution by agrotoxics and untreated sewage discharges. Fish from the Boa Esperança and Guapé sites presented feminisation, intersex and signs of impairment of final oocyte maturation and spawning, evidence of contanimation by xenoestrogen. The expression of zona radiata proteins was detected in male fish from Fama, Boa Esperança and Guapé, strongly suggesting xenoestrogen contamination. In conclusion, the assessment of health indicators and reproductive biomarkers in A. fasciatus provides evidence of the integrated effects of a wide-ranging of environmental contaminants and indicates a need for monitoring and rehabilitation measures of the polluted areas along the Furnas Reservoir in order to preserve its native ictiofauna.